Diet Preferences and Motivations of Female Adolescents: A Descriptive Study in Gorontalo City - Tompunuh, Magdalena M.; Astuti, Siti Choirul Dwi (Yayasan Ahmad Mansyur Nasirah, 2025)
The increasing awareness of the ideal body shape among adolescents, driven by the influence of social media and social pressure, has led many teenage girls to follow specific diet trends despite lacking a thorough understanding of their nutritional needs and the long-term health implications. This study aims to identify the preferred diet trends among teenage girls and to examine their dietary patterns and motivations for dieting, with a focus on female students at SMPN 11 Gorontalo. The research employs a descriptive quantitative approach, with data collected through closed-ended questionnaires distributed to 30 female students in grades VIII and IX who reported having been on or currently being on a diet. The data were analyzed descriptively using percentages and presented in tables and graphs. The results show that the most commonly chosen diet among respondents is the low-carbohydrate diet (36.7%), followed by intermittent fasting (26.7%), portion reduction diets (20%), and vegetarian/vegan diets (10%). Their dietary patterns generally tend to restrict staple food intake and replace it with high-protein foods or fruits. However, this is not always accompanied by an understanding of balanced nutrition. The primary motivations for dieting were the desire to lose weight (43.3%), the influence of social media (30%), and peer encouragement (16.7%). Most respondents obtained their diet-related information from social media, while only a small proportion received information from parents or teachers. These findings suggest that external factors have a greater influence on adolescents' diet preferences than rational health considerations. Therefore, more structured and contextually relevant nutrition education efforts are needed within the school environment to help teenage girls develop healthy, balanced eating habits appropriate to their stage of growth.